Bypassing the law in a homeless vehicle: Alan Bennett's The Lady in the Van - Schniedermann, Wibke; Justus Liebig University Giessen (My University, 2017)
In The Lady in the Van, British playwright Alan Bennett recounts his two-decade acquaintance with a homeless woman who ended up living in a van in his driveway for 15 years. The story has gone through several incarnations, from Bennett s diary entries (published 1989) to a stage play (1999) and a film adaptation (2015). Subverting and disabling the law and its institutions with the help of a vehicle is a key theme in all these versions of the story. Laws regulating the activities and whereabouts of the unhoused poor have notoriously criminalized poverty and excluded the poor from social and economic participation. Legislatures from the 1970s onwards abandoned former attempts to mitigate the circumstances that lead to a loss of shelter. Lawmakers instead adopted a more punitive neoliberal approach that targets homeless individuals through a plethora of new, highly specified illegalities. This essay discusses how Bennett s narrative and its adaptations expose and question the heteronormative, bourgeois-centric practices of anti-homeless laws via a disruption of dominant tropes of poverty and homelessness. Through these subversions, the texts also grapple with the very practical conflicts around invasion of personal space and the mundane inconveniences that are inevitable results of sharing one s private space with a physically and mentally unstable homeless woman. A specific focus will be on the fluidity of the division between public and private spaces that requires constant negotiation within the social microcosm of The Lady in the Van. The socially alien presence of a homeless woman and her unwieldy vehicle complicates the neighbors private and professional lives and, in the process, rattles the structures dictated by different sections of the law, such as parking restrictions, property laws, income support, and traffic regulations.
Keywords: Alan Bennett; The Lady in the Van; homelessness; anti-homeless laws; Homeless Vehicle; ddc:300